MANAJEMEN PENDEKATAN PEMBELAJARAN - Suryapermana, Nana (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
To create a good and perfect learning power is not as easy as turning your palms, or not as difficult as turning your foot. This needs to be studied and reflected in the nature of our minds, so that the learning process does not sink into the abyss of error, which will only destroy the students' learning outcomes, which makes the students do not know the direction, where the step of this learning objective goes. To generate self-confidence, passion and the spirit of student learning, there needs to be a concept of